O turismo e o mundo do campesinato na mesorregião Centro-Ocidental paranaense - Teixeira, Juliana Carolina (2011)
In the same proportion that the process of urbanization advances, grows as well the valorization of the field's life representations. The growth of the demand, characteristic by urban citizens, whom search for the bucolic scenario of countryside, turns these spaces and the quotidian lifestyle in it, objects of consumption to be exchange as a mercantile product through the tourism business. In this context, explode the speeches about the activity as a developing tool to the regions, which suffered with the results of unequal growing promoted by the modernization of agriculture. The rural demography and the rural flight, as result of a modernized agriculture, have compromised the permanency of agriculture workers, whom searched for alternatives to its maintenance. This way, the tourism, one of the non-agricultural activities those, gradually, multiply in the countryside, giving as well to this space a high level of urbanization, stars to be pointed as alternative activity of income to peasants of poorer areas of fields. It is necessary, however, to comprehend that the tourism, as an economic and social business that occurs in this space, also puts itself as another activity of capitalism in the field and, based on the consumption relations, turns the space and everything contained in it into a mercantile product. On the contrary, there is the moral peasant order, based on the rights of people, not in the rights of stuff, where the land is for working, not for business. Supported by this assumptions, this research had as objective to evaluate the presence of tourism as alternative activity of incoming to the peasants of the Central-Occident Mesoregion in Paraná. The dialectical method was used to the realization of this object's study, once it presumes the dynamic and panoramically interpretation of the facts, supporting the analysis of its contradictions. The final results pointed that the existing contradictions between the economic and the social characteristics in the touristic activities and he representations of peasant social actors impedes the growth of the activity with the participation of those same actors in the Central-Occident Mesoregion in Paraná.